ANALYSIS BIOMASS Of SEAGRASSEnhalus acoroidesIN NOTHEAST WATERS PENYENGAT ISLANDOf RIAU ARCHIPELAGO PROVINCE - Prasetya, Dandy; Yoswaty, Dessy; Ghalib, Musrifin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The rapid growth of industrial sectors in various countries leads to an increase in greenhouse gas emissions such as carbon dioxide (CO2) in the atmosphere. One important aspect of reducing carbon gas is the maintenance of forests and oceans to store carbon. One of the potential marine resources for storing CO2 is the seagrass. Waters of the North Sea Penyengat Island has a community of seagrasses composed by various types, one of which is Enhalus acoroides which has an important role as carbon store. This research was conducted in October-November 2017 in the waters of East Sea of Penyengat Island which aims to find out the condition of density and biomass on sea grass in Above ground and Below ground (rhizoma and root) density to seagrass biomass on seagrass. Data were obtained by using the quadratic transect method performed on 4 stations. The results showed that the density of seagrass in the study location was moderate, where the density of seagrass Station III was higher than other stations. The greatest biomass value is found in the rhizomes and roots of seagrasses in all four stations. Less seagrass areas are anthropogenic, ie station III which has a greater biomass potential than the seagrass area with the opposite condition. Keywords: Global warming, Biomass, Seagrass, Penyengat island.